2020
DOI: 10.1002/cbic.202000633
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New DNA Aptamers for Anti‐HIV‐1 Reverse Transcriptase

Abstract: HIV‐1 RT is a necessary enzyme for retroviral replication, which is the main target for antiviral therapy against AIDS. Effective anti‐HIV‐1 RT drugs are divided into two groups; nucleoside inhibitors (NRTI) and non‐nucleoside inhibitors (NNRTI), which inhibit DNA polymerase. In this study, new DNA aptamers were isolated as anti‐HIV‐1 RT inhibitors. The selected DNA aptamer (WT62) presented with high affinity and inhibition against wild‐type (WT) HIV‐1 RT and gave a KD value of 75.10±0.29 nM and an IC50 value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Generally, GNPs have an optical absorption spectrum around 520 nm and show a red color. Aggregation of GNPs shifts their optical absorption spectrum to a higher wavelength at around 630 nm and making them a purple color [ 20 , 21 ]. The complete reaction contained KY DNA aptamer, HIV-1 RT, GNPs, and NaCl and was performed to compare the binding affinity ratio between WT and mutant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, GNPs have an optical absorption spectrum around 520 nm and show a red color. Aggregation of GNPs shifts their optical absorption spectrum to a higher wavelength at around 630 nm and making them a purple color [ 20 , 21 ]. The complete reaction contained KY DNA aptamer, HIV-1 RT, GNPs, and NaCl and was performed to compare the binding affinity ratio between WT and mutant.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that four methionines (M16, M184, M230, and M357) of HIV-1 RT represented the NNRTI drug binding pocket caused by the chemical shift upon binding to NNRTIs. Our previous report investigated the binding complex of HIV-1 RTs and a DNA aptamer by 1 H- 13 C heteronuclear single-quantum coherence (HSQC) and showed that the aptamer affected the NNRTI drug binding pocket of HIV-1 RT [ 20 ]. In this research, we proposed to study the interaction between KY DNA aptamers isolated from KY double mutant HIV-1 RT by NMR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations